Analysis of Designs and Performance of Existing Greenhouse Solar Dryers in Kenya - Ndirangu, S N; Kanali, C L; Mutwiwa, U N; Kituu, G M; Ronoh, E K (Journal of Postharvest Technology, 2018)
Solar drying offers a convenient, cheaper and environmentally friendly way to dry food. In Kenya, solar dryers have been developed and introduced by different actors. However, their technical and economic performance is unknown. This study assessed the technical performance of existing greenhouse dryers in Kenya, by focusing on their design, use and performance. The data was further analysed to identify the correlation between identified parameters. The study was conducted in parts of Eastern and Central regions in Kenya. A total of 18 dryers were sampled from 50 identified dryers. The average size of greenhouse dryers was 8.12 m long, 3.95 m wide and 2.37 m high. The study also analysed designers, selection of construction, internal configuration, and cost of dryers. Generally, a good consideration was noted in these aspects. 24% of dryers experienced losses over 10%. Major causes of losses were cold weather, spillage and poor ventilation. Most dryers achieved good quality products, with 29% getting less than 50% of grade 1. On average, the drying rate was 13, 56, 48 and 64 hours for mangoes, bananas, cassava and butternut, respectively. These drying rates relate well with other studies. Overall, correlation analysis showed consistence in dryer design, use and performance.